Windows XP Just the Steps for Dummies - Stevenson, Nancy (Wiley Publishing, 2011)
The perfect combination of concise instructions and results-oriented visual elements provides readers with a fast and easy understanding of Windows XP essentials Simple, easy-to-follow instructions walk readers through basic Windows XP tasks Covers such topics as navigating the desktop, creating files, copying and deleting files and folders, connecting to the Internet, searching the Web, using e-mail, and much more Minimal front matter, a bargain price, and the clear two-column design come together to make a unique, indispensable resource Covers the latest Service Pack 2 release from Microsoft